Effect of Marine Planktonic Algal Particles on the Communication Performance of Underwater Quantum Link - Zhang, Xiuzai; Ge, Yujie; Saha, AMITAVE (Instrumentation, 2024)
Abstract: As one of the main application directions of quantum technology, underwater quantum communication is of great research significance. In order to study the influence of marine planktonic algal particles on the communication performance of underwater quantum links, based on the extinction characteristics of marine planktonic algal particles, the influence of changes in the chlorophyll concentration and particle number density of planktonic algal particles on the attenuation of underwater links is explored respectively, the influence of marine planktonic algal particles on the fidelity of underwater quantum links, the generation rate of the security key, and the utilization rate of the channel is analyzed, and simulation experiments are carried out. The results show that with the increase in chlorophyll concentration and particle density of aquatic planktonic algal particles, quantum communication channel link attenuation shows a gradually increasing trend. In addition, the security key generation rate, channel fidelity and utilization rate are gradually decreasing. Therefore, the performance of underwater quantum communication channel will be interfered by marine planktonic algal particles, and it is necessary to adjust the relevant parameter values in the quantum communication system according to different marine planktonic algal particle number density and chlorophyll concentration to improve the performance of quantum communication.